Champ religieux et relations de pouvoir. Le pentecôtisme chez les Tobas urbains en Argentine - Tamagno, Liliana; Soldevila, Elena (Anthropologica, 2022)
The aim of this article is to describe and analyze the adoption and resignification of Pentecostalism by the Toba of Argentina. The Iglesia Evangelica Unida ("United Evangelical Church") born in the Province of Chaco as Iglesia Toba ("Toba Church") expresses this people's sociocultural dynamics. It constitutes one of the answers elaborated by the Toba in the face of the transformations imposed upon them first, by colonial expansion, and afterwards, by the formation, consolidation and development of the nation-state. As an organization, this Church reproduces the relations between the Toba and the non-Toba majority, as well as intraethnic relations. Its very existence, its functioning and a sustained search for autonomy show that they did not lose their identity, in spite of the many transformations involved by constant displacements, migrations to the cities.